High-transmittance polyimide material, preparation method and application thereof
Patent Information
- Application Number
- CN202610769871.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-04-20
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-23
AI Technical Summary
[0008]为了解决聚酰亚胺(PI)现有技术中存在难以兼顾高光学透明性和耐热性能的问题以及由此导致其在柔性光电器件中应用受限的问题,本申请提供了一种具有中心咪唑结构的高透光性聚酰亚胺材料技术方案,该材料通过引入中心咪唑结构形成不对称结构聚酰亚胺,并进一步通过长烷基链的取代以进一步提高透光性
[0068]本申请制得的所述高透光性中心咪唑结构聚酰亚胺材料的玻璃化转变温度为250℃以上,初始分解温度(Td5%)在500 ℃以上,残碳率在50%以上。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to a high-transmittance polyimide material, its preparation method, and its application, belonging to the technical field of high-transmittance polymer material preparation. Background Technology
[0002] In recent years, with the rapid development of flexible optoelectronic devices, traditional transparent glass substrates, due to their rigidity and fragility, have become insufficient to meet the demands of flexible displays and wearable electronic devices. Polymer substrates, with their excellent transparency, lightweight, impact resistance, and flexible processing properties, have shown broad application prospects in patterned display devices, liquid crystal alignment layers, optical thin films, organic photovoltaic solar cells, flexible printed circuit boards, and touch screens. However, the manufacturing processes of optoelectronic devices typically require electrode deposition and annealing at high temperatures (e.g., the processing temperature for AMOLED panels needs to reach above 300°C). This necessitates that polymer substrates not only possess high light transmittance but also excellent heat resistance, with their glass transition temperature (Tg) meeting the requirements of high-temperature processes.
[0003] Currently, commercially available transparent polymer materials, such as polyethylene terephthalate (PET, Tg≈78℃), polyethylene naphthalate (PEN, Tg≈120℃), polycarbonate (PC, Tg≈120℃), and polyethersulfone (PES, Tg≈225℃), have relatively low heat resistance temperatures, making them unsuitable for high-performance flexible optoelectronic devices. Furthermore, ideal flexible substrate materials must also possess good dimensional stability, excellent mechanical flexibility, solvent resistance, and a simple film-forming process.
[0004] Polyimide (PI) is considered one of the most promising candidate materials due to its excellent thermal stability, high transparency, superior electrical insulation properties, and mechanical strength, and can be widely used in the microelectronics and optoelectronics industries. However, traditional aromatic PI materials are usually yellow or brown, which severely limits their application in optoelectronic devices. This phenomenon is attributed to the charge-transfer complex (CTC) effect between strong electron donors (such as diaminodiphenyl ether (ODA)) and strong electron acceptors (such as pyromellitic dianhydride (PMDA)) in the PI molecular chain, resulting in tight packing of the molecular chains and strong absorption in the visible light range. The color intensity of PI is closely related to the electron-donating and accepting capabilities of its molecular structure; the stronger the electron-donating and electron-withdrawing capabilities, the more pronounced the CTC effect, and the darker the color of the material.
[0005] Currently, commonly used industrial-grade PI monomers mainly include dianhydrides such as 1S,2S,4R,5R-cyclohexanetetracarboxylic dianhydride (H'PMDA), pyromellitic dianhydride (PMDA), cyclobutanetetracarboxylic dianhydride (CBDA), hexafluoroisopropylphthalic anhydride (6FDA), 3,3′,4,4′-diphenyl ether tetracarboxylic dianhydride (ODPA), and 3,3′,4,4′-benzophenone tetracarboxylic dianhydride (BTDA), as well as diamines such as 2,2′-di(trifluoromethyl)diaminobiphenyl (TFMB) and diaminodiphenyl ether (ODA). Although these monomers can be used to synthesize high-performance PI, relying solely on these structures makes it difficult to simultaneously meet the dual requirements of high temperature resistance and colorless transparency.
[0006] To prepare PI films that combine high light transmittance and high thermal stability, researchers have attempted to suppress the charge-to-catch (CTC) effect through molecular structure design. The main strategies include: 1. Introducing weak electron donor-acceptor structures: using dianhydride monomers with weak electron-withdrawing groups and diamine monomers with weak electron-donating groups to reduce charge transfer between molecular chains; 2. Introducing steric hindrance groups: employing large-volume substituents (such as trifluoromethyl) or asymmetric structures to disrupt the orderly stacking of molecular chains; 3. Introducing alicyclic or non-coplanar structures: reducing conjugation effects and increasing the free volume of molecular chains; 4. Optimizing molecular rigidity: maintaining high thermal stability while controlling optical transparency. However, while weakening the CTC effect improves optical transparency, it usually leads to a decrease in the material's thermal properties; conversely, rigid structures and conjugated systems that enhance thermal stability often exacerbate the CTC effect and reduce light transmittance. Therefore, achieving a balance between optical transparency and thermal resistance is one of the core challenges in developing high-performance colorless and transparent PI materials.
[0007] In summary, there is an urgent need to develop new PI monomers and polymerization strategies to achieve the efficient application of PI materials in flexible optoelectronic devices and meet the comprehensive requirements of high transmittance, high heat resistance and excellent processing performance. Summary of the Invention
[0008] To address the challenge of balancing high optical transparency and heat resistance in existing polyimide (PI) technologies, which limits their application in flexible optoelectronic devices, this application provides a high-transmittance polyimide material with a central imidazole structure. This material introduces a central imidazole structure to form an asymmetric polyimide structure, and further enhances transmittance through the substitution of long alkyl chains. This polymer is synthesized from a diamine monomer with an asymmetric structure and weak electron-donating groups, effectively reducing charge transfer between molecular chains, decreasing the order, symmetry, and stacking of the polyimide molecular chains, increasing the free volume of the molecular chains to some extent, disrupting the conjugation between chains, thereby inhibiting or reducing the formation of intermolecular or intramolecular CTCs (charge-transfer complexes), reducing the absorption of polyimide in the visible light region, and improving the transmittance of the film to prepare a high-temperature resistant, colorless, and transparent film. The high-transmittance central imidazole structured polyimide material exhibits excellent thermal properties, with a glass transition temperature as high as 390 °C; a cutoff wavelength of 360 nm; and a total transmittance of up to 93%. The polymer also demonstrates good solubility in common organic solvents. Compared with currently studied high-transmittance materials, this polymer material shows significant improvements in solubility, thermal properties, and transmittance, possessing potential commercial value and lower production costs, enabling large-scale production and application.
[0009] The technical solution adopted in this application is as follows: According to a first aspect of this application, a high-transmittance polyimide material is provided, characterized in that the high-transmittance polyimide material has the general structural formula shown in Formula I, and has a central imidazole structure; Formula I; Where Ar is a residue of the dianhydride monomer; 0≤x≤12; n = 40~150.
[0010] The structure shown in Formula I is the repeating unit structure of the high-transmittance polyimide material of this application.
[0011] Optionally, the Ar is selected from any group having the structural formula shown in Formula II: Formula II. The asterisk at the end of the horizontal line ( () indicates that the chemical bond is a connection point used to connect other atoms or structural units.
[0012] Optionally, the cutoff wavelength of the high-transmittance polyimide material is less than or equal to 390 nm.
[0013] Optionally, the total light transmittance of the high-transmittance polyimide material is greater than or equal to 80%, and preferably, the highest value of the total light transmittance of the high-transmittance polyimide material is greater than or equal to 93%.
[0014] Optionally, the glass transition temperature of the high-transmittance polyimide material is greater than or equal to 260°C.
[0015] Optionally, the initial decomposition temperature of the high-transmittance polyimide material ( T d5% ) Greater than or equal to 500 ℃.
[0016] Optionally, the residual carbon content of the high-transmittance polyimide material is greater than or equal to 50%.
[0017] Optionally, the molecular weight of the high-transmittance polyimide material is greater than or equal to 30,000 g / mol.
[0018] The core process of the preparation technology of the high-transmittance polyimide material in this application includes: firstly, preparing 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone using benzoin, acetic anhydride, concentrated sulfuric acid, and potassium nitrate as raw materials, and then using the 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone... 1-(4-nitrophenyl)-2-phenylethane-1,2-dione was prepared by deacylation of ethyl ketone under concentrated nitric acid. Then, 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazole was prepared by reacting 1-(4-nitrophenyl)-2-phenylethane-1,2-dione, p-nitrobenzaldehyde, and ammonium acetate in acetic acid. The nitro compound was then reduced to 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazole in the presence of a catalyst and a reducing agent. The diamine monomer 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazole and a dianhydride monomer containing an Ar structure were mixed in an organic solvent and polymerized in a one-step process to prepare polyimide. Finally, the polyimide was alkylated with a bromoalkane via a nucleophilic substitution reaction to obtain alkylated polyimide.
[0019] According to a second aspect of this application, a method for preparing the high-transmittance polyimide material is provided, the preparation method being carried out in an inactive atmosphere, comprising: S1. The starting material containing 1-(4-nitrophenyl)-2-phenylethane-1,2-dione, p-nitrobenzaldehyde, and ammonium acetate is reacted in acetic acid to obtain 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazole (i.e., reaction I yields a nitro compound, and the reaction process is shown in Formula III-1). Formula III-1; S2. 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazolium is reacted in organic solvent I containing catalyst I and reducing agent to obtain 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium (diamine monomer). The reaction process is shown in Formula III-2. Formula III-2; S3. A dianhydride monomer containing 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium and containing an Ar structure is reacted in organic solvent II. A dehydrating agent is added to the reaction system obtained in reaction III to carry out reaction IV. The reaction system of reaction IV is added to organic solvent III to precipitate the product, and a polyimide with a central imidazolium structure is obtained. S4. The polyimide with a central imidazole structure is subjected to a water-removing reaction in an organic solvent III containing catalyst II and a water-removing agent. Bromoalkane is added to the reaction system after the water-removing reaction to carry out a nucleophilic substitution reaction, thereby obtaining the high-transmittance polyimide material (alkylated polyimide with a central imidazole structure). The reaction process is shown in Formula III-3.
[0020] Formula III-3.
[0021] In this application, the inactive atmosphere can be formed by an inert gas.
[0022] Optionally, in step S1, the molar ratio of 1-(4-nitrophenyl)-2-phenylethane-1,2-dione to nitrobenzaldehyde is 1:1 to 1.2.
[0023] Optionally, in step S1, the molar ratio of 1-(4-nitrophenyl)-2-phenylethane-1,2-dione to ammonium acetate is 1:6 to 8.
[0024] Optionally, in step S1, the conditions for reaction I include: a reaction temperature of 120–140 °C and a reaction time of 12–24 h.
[0025] Optionally, in step S1, the ratio of 1-(4-nitrophenyl)-2-phenylethane-1,2-dione to acetic acid is 1 g: 35~50 mL.
[0026] Optionally, in step S1, the reaction of the raw materials containing 1-(4-nitrophenyl)-2-phenylethane-1,2-dione, p-nitrobenzaldehyde, and ammonium acetate in acetic acid to obtain 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazole includes: adding 1-(4-nitrophenyl)-2-phenylethane-1,2-dione and ammonium acetate to acetic acid, heating the reaction system to the temperature of reaction I, and adding a solution of p-nitrobenzaldehyde in acetic acid dropwise (e.g., using a constant pressure dropping funnel) after the above reactants have completely dissolved. After the addition is complete, reaction I is carried out again. After the reaction solution has completely cooled, it is slowly added dropwise to water. During this process, a large amount of orange solid precipitates out. The pH is adjusted to neutral with ammonia water, filtered, washed 3-5 times with deionized water, and finally vacuum dried to obtain 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazole.
[0027] Optionally, in step S2, the conditions for reaction II include: a reaction temperature of 80–120 °C and a reaction time of 18–24 h.
[0028] Optionally, in step S2, the catalyst I is a 5% dry palladium on carbon catalyst (a catalyst containing 5% by mass of metallic palladium and supported on an activated carbon support, based on dry mass). Optionally, in step S2, the reducing agent is 85% hydrazine hydrate (an aqueous solution with a mass fraction of 85% hydrazine hydrate).
[0029] Optionally, in step S2, the organic solvent I is selected from at least one of ethanol, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0030] Optionally, in step S2, the mass ratio of 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazolium to the catalyst is 1:0.05~0.15.
[0031] Optionally, in step S2, the mass ratio of 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazolium to the reducing agent is 1:0.5~1.5.
[0032] Optionally, in step S2, the ratio of 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazolium to organic solvent I is 1:40~50mL.
[0033] Optionally, in step S2, 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazole is reacted in organic solvent I containing catalyst I and reducing agent to obtain 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazole. This includes: adding the dinitro compound 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazole and the catalyst to organic solvent I, then adding the reducing agent dropwise to the above reaction system to carry out reaction II. After the reaction is completed, the mixture is cooled to room temperature, the catalyst is removed by filtration, and the resulting liquid is evaporated to remove the solvent to obtain a solid powder. The powder is then dried in a vacuum drying oven at 75-85 °C for 3-6 h to obtain the product as the diamine monomer 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazole.
[0034] Optionally, in step S3, the ratio of 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium to the dianhydride monomer containing the Ar structure is 1:1 to 1.01.
[0035] Optionally, in step S3, the ratio of 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium to organic solvent II is 1 g: 5~15 mL.
[0036] Optionally, in step S3, the organic solvent II is selected from at least one of m-cresol, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0037] Optionally, in step S3, the conditions for reaction III include: a reaction temperature of 80–200 °C and a reaction time of 16–24 h.
[0038] Optionally, in step S3, the dehydrating agent is isoquinoline (which also acts as a catalyst).
[0039] Preferably, in step S3, the mass ratio of 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazole to the dehydrating agent is 1:0.2~0.8.
[0040] Preferably, in step S3, the organic solvent III is selected from ethanol.
[0041] Optionally, in step S3, the reaction of the dianhydride monomer containing 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium and containing an Ar structure in organic solvent II, the addition of a dehydrating agent to the reaction system obtained in reaction III for reaction IV, and the addition of the reaction system of reaction IV to organic solvent III for product precipitation to obtain a polyimide with a central imidazolium structure, includes: 2,4-Bis(4-aminophenyl)-5-phenyl-1H-imidazolium) is rapidly added to a container (e.g., a three-necked flask), followed by organic solvent II. The reactants are dissolved by stirring at 75–85 °C under a nitrogen atmosphere for 0.5–1.5 h. A dianhydride monomer containing an Ar structure is added to the mixture. Reaction III is carried out by increasing the reaction temperature and continuously stirring, followed by the addition of a dehydrating agent and catalyst. Reaction IV is then carried out by increasing the temperature and stirring. After cooling, the reaction solution is gradually poured into organic solvent III, resulting in a large amount of fibrous precipitate. After filtration, the precipitate is washed with copious amounts of water and ethanol and dried to obtain a polyimide with a central imidazolium structure.
[0042] Optionally, in step S4, the ratio of the polyimide with the central imidazole structure to catalyst II is 1:0.2~0.6.
[0043] Optionally, in step S4, the ratio of the polyimide with the central imidazole structure to the dehydrating agent is 1:11~120.
[0044] Optionally, in step S4, the ratio of the polyimide with the central imidazole structure to organic solvent III is 1 g: 50~80 mL.
[0045] Optionally, in step S4, the water-removing agent is selected from at least one of toluene, xylene, and o-dichlorobenzene.
[0046] Optionally, in step S4, organic solvent III is selected from at least one of N-methylpyrrolidone, N-dimethylformamide, and N-dimethylacetamide.
[0047] Optionally, in step S4, the conditions for the dehydration reaction include: a reaction temperature of 140~160℃ and a reaction time of 1~5h. Under the action of the dehydrating agent, trace amounts of water in the system are removed, and the NH groups are activated simultaneously.
[0048] Optionally, in step S4, the general formula of the bromoalkane is Br(CH2). n CH3, 2 < n < 12.
[0049] Optionally, in step S4, the bromoalkane is bromobutane or bromooctane.
[0050] Optionally, in step S4, the molar ratio of NH groups to bromoalkane in the polyimide with a central imidazole structure is 1:1.0 to 2.0.
[0051] Optionally, in step S4, the conditions for the nuclear substitution reaction include: a reaction temperature of 155–180 °C and a reaction time of 16–48 h.
[0052] Optionally, in step S4, catalyst II is selected from at least one of potassium carbonate, cesium carbonate, and calcium carbonate.
[0053] Optionally, in step S4, the process of reacting the polyimide with a central imidazole structure in an organic solvent III containing catalyst II and a dehydrating agent to remove water, and then adding a bromoalkane to the reaction system after the water removal reaction to carry out a nucleophilic substitution reaction to obtain the high-transmittance polyimide material, includes: sequentially adding the polyimide with a central imidazole structure, catalyst II, organic solvent III, and a dehydrating agent to a container (e.g., a three-necked flask), carrying out the water removal reaction for three hours using the dehydrating agent, releasing excess toluene after the water removal is complete, rapidly adding a bromoalkane after the reaction system has cooled to room temperature, and then heating the reaction system to carry out a nucleophilic substitution reaction. After the reaction system has completely cooled, the reaction solution is poured into an alcohol-water mixture, resulting in the precipitation of a large amount of powdery solids. After standing, the mixture is filtered, washed with hydrochloric acid, filtered again, washed with water 1-3 times, washed with alcohol 1-3 times, and then vacuum dried to obtain the high-transmittance polyimide material.
[0054] Optionally, in step S3, the Ar is selected from any group having the structural formula shown in Formula II: Formula II.
[0055] Optionally, in step S3, the dianhydride monomer containing the Ar structure is selected from at least one of pyromellitic dianhydride (PMDA), biphenyl dianhydride (BPDA), hexafluorodianhydride (6FDA), 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride, and diphenyl ether tetracarboxylic dianhydride (ODPA); for example, the dianhydride monomer containing the Ar structure is 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6-FDA).
[0056] Optionally, in step S1, the preparation step of the 1-(4-nitrophenyl)-2-phenylethane-1,2-dione includes: In an inert atmosphere, benzoin monomer (2-hydroxy-1,2-diphenylethan-1-one) undergoes an oxidative nitration-acylation reaction in acetic anhydride containing concentrated sulfuric acid and potassium nitrate to yield 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone. In this reaction, concentrated nitric acid and acetic anhydride serve as both solvents and reactants. This application strictly limits their proportions; however, those skilled in the art can adjust the ratio of benzoin to acetic anhydride, concentrated sulfuric acid, and potassium nitrate as needed.
[0057] In an inactive atmosphere, 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone was deacylated in concentrated nitric acid to give 1-(4-nitrophenyl)-2-phenylethane-1,2-dione.
[0058] Optionally, the molar ratio of benzoin to acetic anhydride is 1:10 to 45.
[0059] Optionally, the molar ratio of benzoin to concentrated sulfuric acid is 1:3 to 7.5.
[0060] Optionally, the molar ratio of benzoin to potassium nitrate is 1:1 to 2.5.
[0061] Optionally, the reaction conditions for the oxidative nitration acylation reaction include: a reaction temperature of -10 to 25°C and a reaction time of 48 to 72 h.
[0062] Optionally, the molar ratio of 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone to concentrated nitric acid is 1:30 to 50.
[0063] Optionally, the conditions for the deacylation reaction include: a reaction temperature of 90–110 °C and a reaction time of 1–4 h.
[0064] Optionally, the oxidative nitration and acylation reaction of benzoin (2-hydroxy-1,2-diphenylethan-1-one) monomer in acetic anhydride containing concentrated sulfuric acid and potassium nitrate includes: dissolving benzoin in acetic anhydride under ice-water bath conditions and mixing thoroughly, then adding concentrated sulfuric acid dropwise to the solution (exemplarily, a constant pressure dropping funnel can be used), and adding potassium nitrate in batches after the solution becomes clear. The reaction is stirred at this temperature, and the milky white product is dropped into the ice-water mixture to precipitate a yellow-green viscous substance. The substance is then extracted 3-5 times with diethyl ether and 3-5 times with deionized water. After drying the oil phase with anhydrous magnesium sulfate, the substance is recrystallized with alcohol, filtered, and vacuum dried to obtain a white solid product, 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone.
[0065] Optionally, the deacylation reaction of 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone in concentrated nitric acid includes: adding 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone and nitric acid to a container (e.g., a three-necked flask), reacting until the solution changes from yellow transparent to brown transparent. After the reaction is complete, the product is dropped into water, and a large amount of yellow-green solid precipitates out. After filtration, the product is washed 3-5 times with a large amount of deionized water, recrystallized with acetic acid, and finally dried under vacuum to obtain the yellow-green solid product 1-(4-nitrophenyl)-2-phenylethane-1,2-dione.
[0066] According to a third aspect of this application, a high-transmittance polyimide material or a high-transmittance polyimide material prepared according to any of the foregoing methods is provided for use in high-transmittance polymer materials and flexible optoelectronic devices.
[0067] The beneficial effects of this application include: The high-transmittance central imidazole structured polyimide material obtained in this application has a cutoff wavelength of 360-460 nm and a total transmittance of up to 93%.
[0068] The high-transmittance central imidazole structured polyimide material obtained in this application has a glass transition temperature above 250°C and an initial decomposition temperature ( ). T d5% At temperatures above 500 ℃, the residual carbon rate is above 50%.
[0069] The high-transmittance central imidazole structure polyimide obtained in this application has a molecular weight of over 20,000 g / mol. Attached Figure Description
[0070] Figure 1 The NMR spectrum of the prepared polyimide PIDD-6FDA; Figure 2 The NMR spectrum of the prepared polyimide PIDD-6FDA-Ide; Figure 3 The NMR spectrum of the prepared polyimide PIDD-6FDA-Octane; Figure 4 Infrared spectra of the prepared polyimides PIDD-6FDA, PIDD-6FDA-Ide, and PIDD-6FDA-Octane; Figure 5 Differential scanning calorimetry spectra of polyimide PIDD-6FDA, PIDD-6FDA-Ide, and PIDD-6FDA-Octane prepared; Figure 6Thermogravimetric spectra of the prepared polyimide PIDD-6FDA, PIDD-6FDA-Ide and PIDD-6FDA-Octane; Figure 7 The light transmittance test results are for the prepared polyimides PIDD-6FDA, PIDD-6FDA-Ide, and PIDD-6FDA-Octane. Figure 8 The mechanical properties of the prepared polyimides PIDD-6FDA, PIDD-6FDA-Ide, and PIDD-6FDA-Octane are shown in the test results. Detailed Implementation
[0071] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.
[0072] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.
[0073] Unless otherwise specified, all test methods are standard and all instrument settings are those recommended by the manufacturer.
[0074] The data testing conditions and methods used in the embodiments of this application include: Nuclear magnetic resonance spectroscopy (NMR): 1 1H NMR was performed on a Bruker AVANCE III 400 MHz NMR instrument, with tetramethylsilane (TMS) as an internal standard and DMSO- d 6 is the solvent.
[0075] Fourier Transform Infrared (FT-IR) Measurement: FT-IR spectra were obtained using a VERTEX 70 at 4000 cm⁻¹. -1 up to 400 cm -1 Tested within the wavelength range.
[0076] UV-Vis transmittance: Transmittance was measured on a Lambda 950 UV-Vis-NIR spectrophotometer.
[0077] Differential scanning calorimetry (DSC): Measured using a Q20 under nitrogen atmosphere at a heating rate of 10 K / min.
[0078] Thermogravimetric analysis (TG): Measured using a STA449C analyzer under nitrogen atmosphere at a heating rate of 10 K / min.
[0079] Mechanical properties: Tensile testing machine (SHIMADZU, AUTOGRAPH AG-X plus) was used. Sample size: 30 mm in length, 5 mm in width, and 20 μm in thickness. The tensile rate at 30 degrees Celsius was recorded as 0.2 mm / min.
[0080] Example 12, Synthesis of 4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium Step 1: Under an inert gas atmosphere, 8 g of benzoin was dissolved in 40 mL of acetic anhydride in an ice-water bath and mixed thoroughly. Then, 8 mL of concentrated sulfuric acid was added dropwise to the solution using a constant pressure dropping funnel. After the solution became clear, 4.4 g of potassium nitrate was added in portions, and the reaction was stirred at this temperature for 72 hours. The milky white product was added dropwise to the ice-water mixture to precipitate a yellow-green viscous substance. This substance was then extracted five times with diethyl ether and three times with deionized water. The oil phase was dried with anhydrous magnesium sulfate and recrystallized with alcohol. After filtration, the product was dried under vacuum to obtain a white solid product, 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone.
[0081] Step 2: Under an inert gas atmosphere, 11.4158 g of 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone and 70 mL of nitric acid were added to a three-necked flask and reacted at 95 °C for 2 h. The solution changed from yellow transparent to brown transparent. After the reaction was complete, the product was added dropwise to water, and a large amount of yellow-green solid precipitated out. After filtration, the product was washed five times with a large amount of deionized water, recrystallized with acetic acid, and finally dried under vacuum to obtain the yellow-green solid product 1-(4-nitrophenyl)-2-phenylethane-1,2-dione.
[0082] Step 3: Under an inert gas atmosphere, 9.2 g of 1-(4-nitrophenyl)-2-phenylethane-1,2-dione and 22.23 g of ammonium acetate were added to 400 mL of acetic acid. The reaction system was heated to 130°C. After the reactants were completely dissolved, 6.54 g of p-nitrobenzaldehyde dissolved in 20 mL of acetic acid was added dropwise using a constant pressure dropping funnel. After the addition was complete, the reaction mixture was stirred at 130°C for 14 hours. After the reaction solution had completely cooled, it was slowly added dropwise to deionized water. During this process, a large amount of orange solid precipitated. The pH was adjusted to neutral with ammonia water, and the mixture was filtered. It was then washed three to five times with deionized water and finally dried under vacuum to obtain 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazolium.
[0083] Step 4: Under an inert gas atmosphere, 0.446 g of the dinitro compound 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazole and 0.05 g of 10% Pd / C catalyst were added to 20 ml of ethanol. Then, 0.4 ml of hydrazine hydrate was added dropwise to the above reaction system. The reaction was carried out at 85 °C for 12 h. After the reaction was completed, the mixture was cooled to room temperature, the catalyst was removed by filtration, and the solvent was removed by rotary evaporation to obtain a solid powder. The powder was dried in a vacuum drying oven at 80 °C for 6 h to obtain the diamine monomer 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazole.
[0084] Example 2: Synthesis of a central imidazole-structured polyimide polymer Under an inert gas atmosphere, 0.3264 g of 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium was rapidly added to a three-necked flask, followed by approximately 3 mL of m-cresol as a solvent. The mixture was stirred at 80 °C for 1 h under a nitrogen atmosphere to dissolve the reactants. 0.4444 g of 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride (6-FDA) was added to the mixture. The reaction temperature was increased to 150 °C, and stirring was continued. After 3 hours, 0.15 mL of isoquinoline was added to the reaction system as a dehydrating agent and catalyst. The temperature was then increased to 200 °C, and the reaction was continued for 12 h with stirring. After cooling, the reaction solution was gradually poured into ethanol, resulting in a large amount of fibrous precipitate. After filtration, the precipitate was washed with copious amounts of water and ethanol, and the dried product was designated as polyimide PIDD-6FDA. Figure 1 As shown, in 1 In the 1H NMR, 12.91 ppm is the NH peak of PIDD-6FDA imidazole, and 7~8.5 ppm is the Ar-H chemical shift. The structural formula of PIDD-6FDA is as follows:
[0085] like Figure 4 As shown in the FT-IR infrared spectrum, at 1780 and 1720 cm⁻¹... - The peak at ¹ exhibits a typical double peak of asymmetric and symmetric stretching of the imide ring C=O, and at 1375 cm⁻¹ - ¹and 725 cm - The presence of C–N stretching and ring deformation vibration peaks at position ¹ indicates that the diamine and 6FDA successfully condensed to form a polyimide structure. (2500–3500 cm⁻¹) - ¹No significant O–H peaks of carboxylic acids were observed in the high wavenumber region, indicating complete iminolation. For example... Figure 5 In the DSC diagram shown, PIDD-6FDA T g The temperature is 390℃. For example... Figure 6In the TGA diagram shown, PIDD-6FDA T d5 The temperature was 515.4℃, and the char residue rate at 800°C was 62.9%. For example... Figure 7 As shown, UV-Vis transmittance spectroscopy results indicate that the PIDD-6FDA platform has the highest transmittance of approximately 88%. 550nm Its transmittance reaches 84%, and its cutoff wavelength λ cut off The wavelength is 372 nm. The molecular weight (Mn) of the polymer PIDD-6FDA, determined by GPC (gel permeation chromatography), is 109,468,000. Figure 8 As shown, mechanical property tests indicate that the tensile strength of PIDD-6FDA is approximately 64 MPa.
[0086] Example 3: Synthesis of Alkylated Substituted Central Imidazole Polyimide Polymer I Under an inert gas atmosphere, 0.0734 g of polyimide PIDD-6FDA, 0.0326 g of Cs₂CO₃, 5 mL of N,N-dimethylformamide (DMF), and 10 mL of toluene were sequentially added to a 25 mL three-necked flask. The mixture was reacted with toluene at 150 °C for three hours to remove water. After the water removal was complete, excess toluene was released. The reaction system was then cooled to room temperature, and 0.0237 mL of bromobutane was quickly added. The temperature was then raised to 110 °C, and the reaction was carried out at this temperature for 15 hours. After the reaction system had completely cooled, the reaction solution was poured into a mixture of alcohol and deionized water. A large amount of powdery solid precipitated out. After standing, the mixture was filtered, washed with hydrochloric acid, filtered again, washed once with deionized water, washed once with alcohol, and then dried under vacuum to obtain the product, denoted as polyimide PIDD-6FDA-Ide. Figure 2 As shown, in 1 In ¹H NMR, 7–8.5 ppm represents the chemical shift of Ar-H, 4 ppm represents the NMR peak of the α-CH₂ group of substituted imidazole NH, and 0.5–1.5 ppm represents the peak group of long alkyl chains. Figure 4 As shown in the FT-IR infrared spectrum, the concentrations at 1780 and 1720 cm⁻¹ are... - The peak at ¹ exhibits a typical double peak of asymmetric and symmetric stretching of the imide ring C=O, and is located at 1375 cm⁻¹. - ¹and 725 cm - The presence of C–N stretching and ring deformation vibration peaks at position ¹ indicates that the diamine and 6FDA successfully condensed to form a polyimide structure. (2500–3500 cm⁻¹) - ¹No significant O–H peaks for carboxylic acids were observed in the high wavenumber region, indicating complete iminolation. At 2925 and 2853 cm⁻¹ - ¹Aliphatic C–H stretching vibrations appear in the region, and at 1465 cm⁻¹- The region exhibits a CH2 rotational vibration peak, confirming successful side chain grafting. The structural formula of PIDD-6FDA-Ide is as follows:
[0087] like Figure 5 As shown in the DSC diagram, PIDD-6FDA-Ide T g It is 314.62℃. For example... Figure 6 As shown in the TGA diagram, PIDD-6FDA-Ide T d5 The temperature was 475.7℃, and the char residue at 800°C was 57.6%. For example... Figure 7 As shown, UV-Vis transmittance spectroscopy results indicate that the PIDD-6FDA-Ide platform has the highest transmittance of approximately 93%. 550nm Its transmittance reaches 88%, and its cutoff wavelength λ cut off The wavelength is 374 nm. The molecular weight (Mn) of the polymer PIDD-6FDA-Ide was determined to be 7.77 kDa by GPC (gel permeation chromatography). Figure 8 As shown, mechanical property tests indicate that the tensile strength of PIDD-6FDA is approximately 40.66 MPa.
[0088] Example 4 Synthesis of Alkylated Substituted Central Imidazole Polyimide Polymer II Under an inert gas atmosphere, 0.0734 g of polyimide PIDD-6FDA, 0.0162 g of Cs₂CO₃, 5 mL of N,N-dimethylformamide (DMF), and 10 mL of toluene were sequentially added to a 25 mL three-necked flask. The mixture was reacted with toluene at 150 °C for three hours to remove water. After the water removal was complete, excess toluene was released. The reaction system was cooled to room temperature, and 0.0119 mL of bromooctane was quickly added. The temperature was then raised to 110 °C, and the reaction was carried out at this temperature for 15 hours. After the reaction system had completely cooled, the reaction solution was poured into a mixture of alcohol and deionized water. A large amount of powdery solid precipitated out. After standing, the mixture was filtered, washed with hydrochloric acid, filtered again, washed once with deionized water, washed once with alcohol, and then dried under vacuum to obtain the product, denoted as polyimide PIDD-6FDA-Octane. Figure 3 As shown, in 1 In 1H NMR, 7–8.5 ppm represents the chemical shift of Ar-H, 4 ppm represents the NMR peak of the α-CH2 group of the substituted imidazole NH, and 0.5–1.5 ppm represents the peak group of long alkyl chains. The structural formula of PIDD-6FDA-Octane is as follows:
[0089] like Figure 4 As shown in the FT-IR infrared spectrum, the concentrations at 1780 and 1720 cm⁻¹ are... - The peak at ¹ exhibits a typical double peak of asymmetric and symmetric stretching of the imide ring C=O, and at 1375 cm⁻¹ - ¹and 725 cm - The appearance of C–N stretching and ring deformation vibration peaks at position ¹ indicates that the diamine and 6FDA successfully condensed to form a polyimide structure. (2500–3500 cm⁻¹) - ¹No significant O–H peaks for carboxylic acids were observed in the high wavenumber region, indicating complete iminolation. At 2925 and 2853 cm⁻¹ - ¹Aliphatic C–H stretching vibrations appear in the region, and at 1465 cm⁻¹ - The region ¹ exhibits a CH2 rotational vibration peak, confirming successful side chain grafting. For example... Figure 5 As shown in the DSC diagram, PIDD-6FDA-Octane T g It is 253.88℃. For example... Figure 6 As shown in the TGA diagram, PIDD-6FDA-Ide T d5 At 436°C, the residual char rate was 55.4% at 800°C. For example... Figure 7 As shown, UV-Vis transmittance spectroscopy results indicate that the PIDD-6FDA-Octane platform has the highest transmittance of approximately 88%. 550nm Its transmittance reaches 80%, and its cutoff wavelength λ cut off The wavelength is 382 nm. The molecular weight (Mn) of the polymer PIDD-6FDA-Ide was determined to be 3.37 kDa by GPC (gel permeation chromatography). Figure 8 As shown, mechanical property tests indicate that the tensile strength of PIDD-6FDA is approximately 38.53 MPa.
[0090] Table 1 shows a comparison of the heat resistance and light transmittance of the synthesized polyimide in this application embodiment with that of typical commercial polyimides.
[0091] Table 1
[0092] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A high-transmittance polyimide material, characterized in that, The high-transmittance polyimide material has the general structural formula shown in Formula I, and it has a central imidazole structure. Equation I; Where Ar is a residue of the dianhydride monomer; 0≤x≤12; n=40~150。 2. The high-transmittance polyimide material according to claim 1, characterized in that, The Ar is selected from any group having the structural formula shown in Formula II: Formula II.
3. The high-transmittance polyimide material according to claim 1, characterized in that, The cutoff wavelength of the high-transmittance polyimide material is less than or equal to 390 nm; Preferably, the light transmittance of the high-transmittance polyimide material is greater than or equal to 80%; Preferably, the glass transition temperature of the high-transmittance polyimide material is greater than or equal to 260°C; Preferably, the initial decomposition temperature of the high-transmittance polyimide material is ( T d5% ≥500℃; Preferably, the residual carbon content of the high-transmittance polyimide material is greater than or equal to 50%; Preferably, the molecular weight of the high-transmittance polyimide material is greater than or equal to 30,000 g / mol.
4. A method for preparing the high-transmittance polyimide material according to any one of claims 1 to 3, characterized in that, The preparation method is carried out in an inactive atmosphere and includes: S1. The raw material containing 1-(4-nitrophenyl)-2-phenylethane-1,2-dione, p-nitrobenzaldehyde and ammonium acetate is reacted in acetic acid to obtain 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazolium; S2. 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazole is reacted in organic solvent I containing catalyst I and reducing agent to obtain 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazole; S3. A dianhydride monomer containing 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium and containing an Ar structure is reacted in organic solvent II. A dehydrating agent is added to the reaction system obtained in reaction III to carry out reaction IV. The reaction system of reaction IV is added to organic solvent III to precipitate the product, and a polyimide with a central imidazolium structure is obtained. S4. The polyimide with a central imidazole structure is subjected to a water-removing reaction in an organic solvent III containing catalyst II and a water-removing agent. Bromoalkane is added to the reaction system after the water-removing reaction to carry out a nucleophilic substitution reaction, thereby obtaining the high-transmittance polyimide material.
5. The preparation method according to claim 4, characterized in that, In step S1, the molar ratio of 1-(4-nitrophenyl)-2-phenylethane-1,2-dione to nitrobenzaldehyde is 1:1 to 1.2; Preferably, in step S1, the molar ratio of 1-(4-nitrophenyl)-2-phenylethane-1,2-dione to ammonium acetate is 1:6-8; Preferably, in step S1, the conditions for reaction I include: a reaction temperature of 120–140 °C and a reaction time of 12–24 h; Preferably, in step S1, the ratio of 1-(4-nitrophenyl)-2-phenylethane-1,2-dione to acetic acid is 1 g: 35~50 mL.
6. The preparation method according to claim 4, characterized in that, In step S2, the conditions for reaction II include: a reaction temperature of 80–120 °C and a reaction time of 18–24 h; Preferably, in step S2, catalyst I is a 5% dry palladium on carbon catalyst; Preferably, in step S2, the reducing agent is 85% hydrazine hydrate; Preferably, in step S2, the organic solvent I is selected from at least one of ethanol, N,N-dimethylformamide, and N,N-dimethylacetamide; Preferably, in step S2, the mass ratio of 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazolium to the catalyst is 1:0.05~0.15; Preferably, in step S2, the mass ratio of 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazolium to the reducing agent is 1:0.5~1.5; Preferably, in step S2, the ratio of 2,4-bis(4-nitrophenyl)-5-phenyl-1H-imidazole to organic solvent I is 1:40~50mL.
7. The preparation method according to claim 4, characterized in that, In step S3, the ratio of 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium to the dianhydride monomer containing the Ar structure is 1:1 to 1.01; Preferably, in step S3, the ratio of 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium to organic solvent II is 1g:5~15mL; Preferably, in step S3, the organic solvent II is selected from at least one of m-cresol, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; Preferably, in step S3, the conditions for reaction III include: a reaction temperature of 80–200 °C and a reaction time of 16–24 h; Preferably, in step S3, the dehydrating agent is isoquinoline; Preferably, in step S3, the mass ratio of 2,4-bis(4-aminophenyl)-5-phenyl-1H-imidazolium to the dehydrating agent is 1:0.2~0.8; Preferably, in step S3, the organic solvent III is selected from ethanol.
8. The preparation method according to claim 4, characterized in that, In step S4, the ratio of polyimide with a central imidazole structure to catalyst II is 1:0.2~0.6; Preferably, in step S4, the ratio of the polyimide with the central imidazole structure to the dehydrating agent is 1:11~120; Preferably, in step S4, the ratio of the polyimide with the central imidazole structure to organic solvent III is 1 g: 50~80 mL; Preferably, in step S4, the dehydrating agent is selected from at least one of toluene, xylene, and o-dichlorobenzene; Preferably, in step S4, organic solvent III is selected from at least one of N-methylpyrrolidone, N-dimethylformamide, and N-dimethylacetamide; Preferably, in step S4, the conditions for the reaction with water include: a reaction temperature of 140~160℃ and a reaction time of 1~5 h; Preferably, in step S4, the general formula of the bromoalkane is Br(CH2). n CH3, 2 < n < 12; Preferably, in step S4, the bromoalkane is bromobutane or bromooctane; Preferably, in step S4, the molar ratio of NH groups to bromoalkane in the polyimide with a central imidazole structure is 1:1.0 to 2.0; Preferably, in step S4, the conditions for the nuclear substitution reaction include: a reaction temperature of 155–180 °C and a reaction time of 16–48 h; Preferably, in step S4, catalyst II is selected from at least one of potassium carbonate, cesium carbonate, and calcium carbonate.
9. The preparation method according to claim 4, characterized in that, In step S3, the Ar is selected from any group having the structural formula shown in Formula II: Formula II; Preferably, in step S3, the dianhydride monomer containing the Ar structure is selected from at least one of pyromellitic dianhydride, biphenyl dianhydride, hexafluorodianhydride, and diphenyl ether dianhydride. Preferably, in step S1, the preparation step of the 1-(4-nitrophenyl)-2-phenylethane-1,2-dione includes: In an inactive atmosphere, benzoin monomer is subjected to an oxidative nitration acylation reaction in acetic anhydride containing concentrated sulfuric acid and potassium nitrate to give 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone; In an inactive atmosphere, 1-(4-nitrophenyl)-2-phenyl-2-(1-propen-2-oxy) ethyl ketone was deacylated in concentrated nitric acid to give 1-(4-nitrophenyl)-2-phenylethane-1,2-dione; Preferably, the reaction conditions for the oxidative nitration acylation reaction include: a reaction temperature of -10 to 25 °C and a reaction time of 48 to 72 h; Preferably, the conditions for the deacylation reaction include: a reaction temperature of 90–110 °C and a reaction time of 1–4 h.
10. The high-transmittance polyimide material according to any one of claims 1 to 3 or the high-transmittance polyimide material obtained by the preparation method according to any one of claims 4 to 9 is used in high-transmittance polymer materials and flexible optoelectronic devices.